Demonstration of compost making from kitchen and garden waste - Mohamed, Bebe Norlita; Mohd Khairlani, Nurul Hidayah; Wondi, Mohd Hafizz; Mansur, Nurul Syahirah; Sulaiman, Muhamad Nasarudin (Corporate Communication Unit, UiTM Mukah Campus, 2025)
In conjunction with the Community Program for Raising Awareness on Open Burning under the Sustainable Management of Peatland Ecosystem in Malaysia (SMPEM) Project 2025, a session on the preparation of compost fertilizer from kitchen waste was held. The main objective of the session was to educate the local community on sustainable waste management practices by recycling kitchen and garden waste into compost fertilizer. Compost fertilizer produced from kitchen and garden waste is often rich in nutrients that enhance soil fertility.